2019
DOI: 10.3390/s19143137
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Embedded Myokinetic Prosthetic Hand Controller

Abstract: The quest for an intuitive and physiologically appropriate human machine interface for the control of dexterous prostheses is far from being completed. In the last decade, much effort has been dedicated to explore innovative control strategies based on the electrical signals generated by the muscles during contraction. In contrast, a novel approach, dubbed myokinetic interface, derives the control signals from the localization of multiple magnetic markers (MMs) directly implanted into the residual muscles of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 16 publications
1
23
0
Order By: Relevance
“…For instance, having a magnet implanted in each target muscle would provide highly selective control signals compared to surface measurements, like those available in Force Myography 22 . The relatively small dimensions of the external sensor boards and control electronics, envisioned to be fully integrated into the socket 16 , would make the system convenient and easy-to-wear when compared, for example, with ultrasound probes used in sonography 23 . Future clinical trials will allow to quantitatively and qualitatively assess such advantages and to make a more thorough comparison with state-of-the-art solutions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, having a magnet implanted in each target muscle would provide highly selective control signals compared to surface measurements, like those available in Force Myography 22 . The relatively small dimensions of the external sensor boards and control electronics, envisioned to be fully integrated into the socket 16 , would make the system convenient and easy-to-wear when compared, for example, with ultrasound probes used in sonography 23 . Future clinical trials will allow to quantitatively and qualitatively assess such advantages and to make a more thorough comparison with state-of-the-art solutions.…”
Section: Discussionmentioning
confidence: 99%
“…Several applications, including the one proposed by our group, would highly benefit from an increase in the number of simultaneously trackable MMs 8 , 12 , 15 . In our first work, we proved the viability of a system able to localize the position of four MMs 8 virtually implanted in an anatomically relevant forearm mockup; in a more recent study 16 , we demonstrated an embedded system capable of localizing up to five MMs, in real-time. Besides the practical implementation of the system, we investigated how the accuracy, the precision and the computation time of the localizer are affected by the number and distribution of both the MMs and the sensors 14 .…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…In the following works [ 150 , 151 ], researchers assessed the accuracy of the position tracking of multiple magnetic markers with a set of magnetic field sensors. It was found that increasing number of magnets (and decreasing available space between them) causes localization errors and false predictions to occur more often.…”
Section: Promising Control Approachesmentioning
confidence: 99%
“…where accounts for inaccuracies in tracking the displacement of the moving magnet (i.e., model error), while accounts for false predictions of simultaneous displacement affecting the non-moving magnets (i.e., crosstalk effect). and were defined as the Euclidean distance between the actual and the estimated displacement for the moving and non-moving MMs, respectively, akin to our previous works [10], [14], [15], [26].…”
Section: Localization Problemmentioning
confidence: 99%